Integrated Alternative Source of Energy System with Grid Substation - Shyamsundar Gupta; Sankalp Saurabh; A.K. Akella (Institute of Advanced Engineering and Science, 2015)
This paper discusses the modeling, simulation and optimization of integrated alternative source of energy system with grid substation. When there is a lack of energy in grid substation to meet the demand of customer load then alternative source of energy compensates energy deficiency and after that if there is excess energy available then remaining energy is stored in battery bank or sells to grid according to need. In another case when required energy is not generated by alternative sources then remaining energy is purchased from the grid and if the grid substation hasn’t available these remaining energy to meet the customer load demand during the peak load then stored battery energy is also active. The size of integrated alternative source of energy system may vary from few hundred watts to ten or hundreds of MW. The possible sources of alternative energy like solar, wind and biomass are considered under this paper. Study location, Muzaffarpur district of Bihar (India), is taken because there is good potential of energy generation from alternative source of energy and still there is no any wind and solar energy power plant. The modeling and simulation of the system is done by using HOMER software and the software solve the optimization problem to minimize the total cost of system and maximum utilization of alternative source of energy.